Perspective: Use of protein S100B as a quality assurance marker for endovascular therapy in acute ischemic stroke - Lieschke, Franziska; Foerch, Christian (Frontiers in Neurology, 2025)
Mechanical thrombectomy (MT) is a highly effective treatment for ischemic stroke associated with large vessel occlusion. Given its complexity, this procedure is widely used throughout the world in hospitals with different levels of experience. Therefore, practical quality assurance is advised to ensure a high standard of care across the board. In this perspective article, we propose the implementation of measuring serum S100B after MT as a surrogate outcome parameter for the extent of tissue damage as an additional quality indicator for internal and external benchmarking in endovascular therapy. We focus on the analysis of patients, in whom there is a discrepancy between the expected (e.g., based on favorable preconditions) and the actual biomarker outcome. We aim to illustrate the advantages and drawbacks of measuring S100B after MT, reliably depicting the procedure’s quality and its use for comparison and identification of “outlier” patients in MT patient cohorts for further process and single-case analysis.